Defending against Speculative Attacks - Tijmen R. Daniels; Henk Jager; Franc Klaassen (Tinbergen Institute, 2008)
While virtually all modern models of exchange rate crises recognise that the decision to abandon an exchange rate peg depends on how harshly policy makers are willing to defend the regime, they virtually never model how the exchange rate is defended. In this paper we incorporate both the mechanics of speculation and a defence policy against speculation in the well-known currency crisis model of Morris and Shin (American Economic Review 88 (1998) 587-97). After adding these natural elements, our model outperforms standard currency crisis models at explaining stylised features of speculative attacks. Moreover, our model connects the theoretical currency crisis literature to an empirical literature on exchange market pressure, by bringing together its building blocks: exchange rate changes plus counter-acting defence policies. We use this connection to confirm our model's predictions empirically.
Keywords: E58; F31; F33; G15; 330; Exchange Market Pressure; Currency Crisis; Global Game; Währungsspekulation; Währungskrise; Wechselkurspolitik; Devisenmarkt; Spieltheorie; Theorie